PENERAPAN FRAUD DIAMOND DALAM PENDETEKSIAN KECURANGAN LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Healthcare yang Terdaftar di BEI 2019-2022) - Haq, Shifna Zihdatal; Rahardjo, Shiddiq Nur (Diponegoro Journal of Accounting, 2024)
This study was conducted to analyze the effect of the fraud diamond concept proposed by Wolfe and Hermanson, that financial targets, effective monitoring, audit opinion and broad director change as independent variable towards financial statement fraud as variabel dependent proxied by the Beneish M-Score formula.The samples used in this study are 19 heatlhcare companies listed during the period 2019-2022 in the Indonesia Stock Exchange. Hypothesis testing was conducted using the logistic regression method with SPSS 25 software.The results showed that the effective monitoring variable proxied by the ratio of the number of independent commissioners to the total number of commissioners and the board of directors turnover variable proved to have an effect on financial statement fraud. Meanwhile, for the financial target variable proxied by return on assets and audit opinion in this study does not prove that these variables have an effect on financial statement fraud.